2021
DOI: 10.5194/egusphere-egu21-7376
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low density-microplastics detected in sheep faeces and soil: A case study from the intensive vegetable farming in Southeast Spain

Abstract: <p>One of the main sources of plastic pollution in agricultural fields is the plastic mulch used by farmers to improve crop production. The plastic mulch is often not removed completely from the fields after harvest. Over time, the plastic mulch that is left of the fields is broken down into smaller particles which are dispersed by the wind or runoff. In the Region of Murcia in Spain, plastic mulch is heavily used for intensive vegetable farming. After harvest, sheep are released into the fields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…This literature review suggests that an abundance of microplastics has been found in human feces, meaning its existence is beyond doubt. Another study which corroborates that microplastics evidence is also found in feces is microplastics research in animal feces such as microplastics found in 92% of sheep feces [26], 55% of the most common microplastics and 41% of microplastics fibers found in seal feces [27] and 47% of feces precursor samples in seabirds [28].…”
Section: Microplastics In Human Specimensupporting
confidence: 59%
“…This literature review suggests that an abundance of microplastics has been found in human feces, meaning its existence is beyond doubt. Another study which corroborates that microplastics evidence is also found in feces is microplastics research in animal feces such as microplastics found in 92% of sheep feces [26], 55% of the most common microplastics and 41% of microplastics fibers found in seal feces [27] and 47% of feces precursor samples in seabirds [28].…”
Section: Microplastics In Human Specimensupporting
confidence: 59%